Thyroidectomy Under Local Anesthesia: A Viable, Safe, and Effective Alternative to General Anesthesia - K. C. Sunil; H. R. Divya; Sunitha Singh (Journal of Head & Neck Physicians and Surgeons)
Objective: The objectives of this study were to evaluate the viability, safety, and effectiveness of thyroidectomy under local anesthesia as an alternative to general anesthesia. Materials and Methods: A prospective study was conducted at a tertiary care institute from January to June 2024. Thirty-three euthyroid patients with unilateral benign thyroid disease underwent hemithyroidectomy under local anesthesia with cervical plexus regional and anterior field blocks, supplemented with intravenous midazolam. Primary outcomes measured included operative duration, conversion to general anesthesia, complications, and limitations. Results: The participants included 31 females and 2 males (mean age 42.2 years). The mean operative time was 47 min (range 30–70 min). No conversions to general anesthesia were required. Complications were minimal: two cases of temporary vocal cord palsy, and isolated cases of seroma, hematoma, and wound dehiscence. All patients were discharged within 24 h. Pathological findings revealed predominantly colloid goiter (60%), with six incidental carcinomas requiring completion thyroidectomy, also performed under local anesthesia. No cases of hypoparathyroidism or permanent nerve injury were observed during the 12–24-week follow-up period. Conclusion: Thyroidectomy under local anesthesia is a safe, viable, and effective alternative to general anesthesia in carefully selected patients. The technique offers advantages including immediate postoperative voice assessment, faster recovery, shorter hospital stay, and cost-effectiveness. Success depends on appropriate patient selection and careful intraoperative monitoring. This approach can be implemented to optimize surgical outcomes and resource utilization.